A Rare Case of Acute Ischemic Pancreatitis and Duodenitis in the Setting of Cardiogenic Shock - Binyamin Ravina Abramowitz; Nealansh Embre Gupta; Syeda Maleehah Ali; Bani Chander Roland; Daniel Anthony DiLeo (Case Reports in Gastrointestinal Medicine)
Acute ischemic pancreatitis and duodenitis are uncommon diagnoses that can affect patients with shock. As respiratory, cardiac, and neurological manifestations of shock are prioritized, resultant gastrointestinal (GI) related pathologies can be overlooked, leading to underdiagnosis of these conditions. In this report, we highlight the importance of recognizing acute ischemic pancreatitis and duodenitis in our description of a unique patient presenting with GI related complaints with underlying cardiogenic shock.